The Relationship Between Pregnant Women's Knowledge About Pregnancy Nutrition and the Incidence of Chronic Energy Deficiency (CED) - Nurjanah Abubakar; Rani Safitri; Nila Widya Keswara (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Chronic energy deficiency (CED) in pregnalnt women is al problem thalt still occurs todaly. Chronic energy deficiency in pregnalnt women caln halve aln impalct on the heallth of the mother during pregnalncy, childbirth alnd the heallth conditions of the child who will be born. The purpose of this study is to determine the relaltionship between the level of knowledge albout nutrition alnd the incidence of chronic energy deficiency (CHD) in pregnalnt women alt the Siko Heallth Center. This study used al descriptive correlaltion design with al cross sectionall alpproalch. Daltal alnallysis used the Chi Squalre test method. This study wals conducted with al salmple of 1l0l4 people. The results showed al relaltionship between the level of knowledge The results showed thalt there wals al relaltionship between the level of knowledge albout nutrition alnd the incidence of chronic energy deficiency (CHD) in pregnalnt women alt the Siko Heallth Center, with al p-vallue of 0l.0l0l0l <0l.0l5. Nurses als palrt of heallth workers plaly aln importalnt role in efforts to increalse pregnalnt women's nutritionall knowledge so thalt the nutrition of pregnalnt women caln be fulfilled. nutrition of pregnalnt women caln be fulfilled optimallly to prevent the occurrence of SEZ.